Prevalence and risk factors of HIV infection among people who inject drugs in Cambodia: findings from a national survey - Gitau Mburu; Pheak Chhoun; Navy Chann; Sovannary Tuot; Phalkun Mun; Siyan Yi (BMC, 2019)
Abstract Background Globally, people who inject drugs (PWID) continue to be among the most vulnerable populations to acquire infection of human immunodeficiency virus (HIV). The most recent national survey found that nearly a quarter of PWID in Cambodia were infected with HIV in 2012. The aim of this study is to estimate the current prevalence of and factors associated with HIV infection among PWID in Cambodia. Methods This national integrated biological and behavioral survey was conducted from June to December 2017. Participants were recruited from the capital city and 11 major provinces using the respondent driven sampling method. Face-to-face interviews were conducted using a structured questionnaire, and blood samples were collected for HIV, syphilis, and hepatitis C virus (HCV) testing. Multiple logistic regression analysis was conducted to identify risk factors for HIV infection. All analyses were estimated with sampling weights that corrected for non-response and sample design. Results A total of 310 PWID participated in the study, and the mean age was 31.8 years (SD = 7.8). The prevalence of HIV was 15.2%. More than half (57.4%) of the HIV-positive participants were co-infected with HCV, and 44.7% were not aware of their HIV status prior to this study. After adjustment for other covariates, HIV infection remained positively associated with being female (AOR = 1.88, 95% CI = 1.03-4.04), being in the older age group of ≥35 (AOR = 2.99, 95% CI 1.33-9.22), being widowed, divorced or separated (AOR = 2.57, 95% CI = 1.04-6.67), living on the streets (AOR = 2.86, 95% CI 1.24-4.37), and HCV infection (AOR = 3.89, 95% CI 1.86-1.15). The HIV infection remained negatively associated with having higher level of formal education of ≥10 years (AOR = 0.44, 95% CI 0.13-0.83) and higher average income of ≥US$200 per month (AOR = 0.20, 95% CI = 0.05-0.74). Conclusions The prevalence of HIV among PWID in Cambodia remains high, but is reducing compared with the 24.8% reported in the 2012 national survey. Findings from this study provide critical information for tailoring interventions based on identified vulnerabilities and risk factors for HIV. Our findings underline the importance of socio-structural factors in HIV epidemiology among PWID in Cambodia, which require mitigation.